Possibilities d'Agregation de Fonctions de Production a Variables Capital et Main d'Oeuvre - Nataf, A. (Review of Economic Studies, 1967)
Journal Article Possibilites d'Agregation de Fonctions de Production a Variables Capital et Main d'Oeuvre Get access A. Nataf A. Nataf Faculté des Sciences de Caen and CERMAP Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 2, April 1967, Pages 219–226, https://doi.org/10.2307/2296810 Published: 01 April 1967